background image

Remark 16.16.

Most typically

G

is the group of translations of some topological vector space.

Generalized limit

is dened by the following formula:

Denition 16.17.

xlim

f

=

def

f

f

 "

r

j

r

2

G

g

for any funcoid

f

.

Remark 16.18.

Generalized limit technically is a set of funcoids.

We will assume that dom

f

w h

i

f

x

g

.

Denition 16.19.

xlim

x

f

=

def

xlim

f

j

h

i

f

x

g

.

Obvious 16.20.

xlim

x

f

=

f

f

j

h

i

f

x

g

"

r

j

r

2

G

g

.

Remark 16.21.

xlim

x

f

is the same for funcoids

and Compl

.

The function

will dene an injection from the set of points of the space

(numbers, points,

or vectors) to the set of all (generalized) limits (i.e. values which xlim

x

f

may take).

Denition 16.22.

(

y

) =

def

fh

i

f

x

FCD

h

i

f

y

g j

x

2

D

g

.

Proposition 16.23.

(

y

) =

f

(

h

i

f

x

FCD

h

i

f

y

g

)

 "

r

j

r

2

G

g

for every (xed)

x

2

D

.

Proof.

(

h

i

f

x

FCD

h

i

y

)

 "

r

=

h"

r

¡

1

ih

i

f

x

FCD

h

i

y

=

h

ih"

r

¡

1

i

f

x

FCD

h

i

y

=

h

i

f

r

¡

1

x

FCD

h

i

y

2 fh

i

f

x

FCD

h

i

f

y

g j

x

2

D

g

.

Reversely

h

i

f

x

FCD

h

i

f

y

g

= (

h

i

f

x

FCD

h

i

f

y

g

)

 "

e

where

e

is the identify element

of

G

.

Proposition 16.24.

(

y

) =

xlim

¡

h

i

f

x

FCD

"

Base

(

Ob

)

f

y

g

(for every

x

). Informally: Every

(

y

)

is a generalized limit of a constant funcoid.

Proof.

xlim

¡

h

i

f

x

FCD

"

Base

(

Ob

)

f

y

g

=

¡

h

i

f

x

FCD

"

Base

(

Ob

)

f

y

g

 "

r

j

r

2

G

 

=

f

(

h

i

f

x

FCD

h

i

f

y

g

)

 "

r

j

r

2

G

g

=

(

y

)

.

Theorem 16.25.

If

f

j

h

i

f

x

g

2

C

(

;

)

and

h

i

f

x

g w "

Ob

f

x

g

then xlim

x

f

=

(

fx

)

.

Proof.

f

j

h

i

f

x

g

v

f

j

h

i

f

x

g

v

f

; thus

h

f

ih

i

f

x

g v h

ih

f

i

f

x

g

; consequently we have

w h

ih

f

i

f

x

FCD

h

ih

f

i

f

x

g w h

f

ih

i

f

x

FCD

h

ih

f

i

f

x

g

:

f

j

h

i

f

x

g

w

(

h

f

ih

i

f

x

FCD

h

ih

f

i

f

x

g

)

f

j

h

i

f

x

g

=

h

(

f

j

h

i

f

x

g

)

¡

1

ih

f

ih

i

f

x

FCD

h

ih

f

i

f

x

g w

id

dom

f

j

h

if

x

g

FCD

h

i

f

x

FCD

h

ih

f

i

f

x

g w

dom

f

j

h

i

f

x

g

FCD

h

ih

f

i

f

x

g

=

h

i

f

x

FCD

h

ih

f

i

f

x

g

:

im

(

f

j

h

i

f

x

g

) =

h

ih

f

i

f

x

g

;

f

j

h

i

f

x

g

v

h

i

f

x

FCD

im

(

f

j

h

i

f

x

g

) =

h

i

f

x

FCD

h

ih

f

i

f

x

g

:

So

f

j

h

i

f

x

g

=

h

i

f

x

FCD

h

ih

f

i

f

x

g

.

Thus xlim

x

f

=

f

(

h

i

f

x

FCD

h

ih

f

i

f

x

g

)

 "

r

j

r

2

G

g

=

(

fx

)

.

Remark 16.26.

Without the requirement of

h

i

f

x

g w "

Ob

f

x

g

the last theorem would not work

in the case of removable singularity.

16.4 Generalized limit

201